До характеристики суб’єктів забезпечення дисципліни та законності в діяльності Державного бюро розслідувань - Старченко, В. М.; Starchenko, V. M. (Право.ua. - 2022. - № 1. - С. 235-240, 2022)
Встановлено, під суб’єктом забезпечення дисципліни та законності в Державному бюро розслідувань найбільш доцільно розуміти спеціально уповноважену фізичну та/або юридичну особу, яка відповідно до норм чинного законодавства наділена необхідною сукупністю владних повноважень задля ефективного вирішення завдань, пов’язаних із створенням правових та організаційних умов, за яких службовці даного відомства будуть неухильно дотримуватись норм, вимог та стандартів у діяльності даного відомства. Виокремлено коло суб’єктів забезпечення дисципліни та законності в Державному бюро розслідувань. Наголошено, що відповідна система є досить розгалуженою, а кожен із окреслених в статті суб’єктів володіє своїм, особливим правовим статусом. Відзначено, що одне із ключових місць в системі досліджуваних суб’єктів займає саме керівник Державного бюро розслідувань.

It is established that under the subject of ensuring discipline and legality in the State Bureau of Investigation, it is most expedient to understand a specially authorized natural and/ or legal entity, which, in accordance with the norms of current legislation, is endowed with the necessary set of powers for the effective solution of tasks related to the creation of legal and organizational conditions under which the employees of this department will strictly observe the norms, requirements and standards in the activities of this department. The circle of subjects for ensuring discipline and legality in the State Bureau of Investigation has been singled out. It is emphasized that the corresponding system is quite extensive, and each of the subjects outlined in the article has its own, special legal status. It was noted that one of the key positions in the system of investigated subjects is occupied by the head of the State Bureau of Investigation. This is explained by the fact that he: firstly, possesses a wide range of tools, which gives him the opportunity to exert managerial and disciplinary influence on the personnel of the Bureau’s bodies and units; secondly, unlike many other subjects, the head is in the “middle” of the structure of the SBI, directly manages its elements (bodies and units), and therefore has more opportunities to promptly solve current tasks in the field of ensuring legality and discipline in functioning of this department; thirdly, carries out direct, current and systematic control over the state of work of subordinate bodies and units, which makes it possible to warn and timely detect and stop violations in the process of activities of persons subordinate to him; fourthly, applies measures of disciplinary responsibility for violations of labor discipline; fifthly, he conducts educational activities among his subordinate team, which is an important preventive means of ensuring discipline in the process of official activity.

Установлено, что под субъектом обеспечения дисциплины и законности в Государственном бюро расследований наиболее целесообразно понимать специально уполномоченное физическое и/или юридическое лицо, которое в соответствии с нормами действующего законодательства наделено необходимой совокупностью властных полномочий для эффективного решения задач, связанных с созданием правовых и организационных условий, при которых служащие данного ведомства будут неукоснительно соблюдать нормы, требования и стандарты в деятельности данного ведомства. Выделены круг субъектов обеспечения дисциплины и законности в Государственном бюро расследований. Отмечено, что соответствующая система достаточно разветвленная, а каждый из очерченных в статьи субъектов владеет своим, особым правовым статусом. Отмечено, что одно из ключевых мест в системе исследуемых субъектов занимает руководитель Государственного бюро расследований.
Keywords: Державне бюро розслідувань; правовий статус; суб’єкти забезпечення дисципліни та законності; керівник; State Bureau of Investigation; legal status; subjects of ensuring discipline and legality; head; Государственное бюро расследований; правовой статус; субъекты обеспечения дисциплины и законности; руководитель